Composition, ceramsite composition, ceramsite and preparation method thereof
By using a specific proportion of Ca(OH)2, CaCO3 and free carbon as gas-generating substances, combined with bentonite, fly ash and red mud, low density and high strength ceramic granules are prepared, which solves the problems of high density and poor strength of ceramic granules, and achieves resource conservation and performance improvement.
Patent Information
- Application Number
- CN202411994003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
AI Technical Summary
With the scarcity of natural resources, finding alternative raw materials to prepare light clay has become an urgent need, and the prior art is difficult to effectively reduce the density of ceramic particles and improve its strength.
Ca(OH)2, CaCO3 and free carbon with a mass ratio of 32-45:5-10:9-15 are used as gas-generating substances, and clay granules are prepared in combination with bentonite, fly ash and red mud. By controlling the proportion of free carbon and the amount of calcium hydroxide, the gas-generating effect and structure of clay granules are regulated.
In the case of low usage, the density of the ceramide is significantly reduced and its strength is improved. The bulk density is 400 kg/m3 to 600 kg/m3, the water absorption is 3 to 12%, and the cylinder pressure strength is 3.0 MPa to 6.0 MPa.
Smart Images

Figure BDA0005224215730000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a composition, a ceramsite composition, ceramsite and a preparation method thereof. Background Art
[0002] Ceramic aggregate has excellent properties such as light weight, high strength, high porosity, thermal insulation, corrosion resistance, earthquake resistance, and resistance to alkali aggregate reaction. It is widely used in engineering in the fields of building materials, refractory insulation materials, petroleum, and chemical industry. At present, the main raw materials for the production of ceramsite are natural raw materials such as shale, clay, and silt from rivers, seas, and lakes.
[0003] The principle of preparing lightweight ceramsite is generally that the material itself is gasified and closed pores are formed inside. According to the different properties of ceramsite, ceramsite can be used as concrete aggregate, filter material in the water treatment industry, carrier of slow-release fertilizer in agriculture, etc. At present, with the restricted mining of natural resources and the restrictions of environmental protection policies, resources such as clay and shale are becoming increasingly scarce. Therefore, it is inevitable to seek other raw materials to prepare lightweight clay. Summary of the invention
[0004] In view of this, the present invention provides a composition, a ceramsite composition, ceramsite and a preparation method thereof. The composition provided in the present application has a good gas generating effect and can reduce the density of the obtained ceramsite and improve its strength when used in a low dosage.
[0005] The present application provides a composition comprising Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32-45:5-10:9-15.
[0006] In some specific implementations, the composition includes:
[0007] Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:9;
[0008] or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:12;
[0009] or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:15;
[0010] or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32:5:12;
[0011] Or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 45:5:12.
[0012] The present application provides a ceramsite composition, comprising:
[0013] 5 to 20 parts by weight of bentonite;
[0014] 10 to 50 parts by weight of the composition described in the above technical solution;
[0015] 20 to 60 parts by weight of fly ash;
[0016] 0 to 30 parts by weight of red mud.
[0017] In some specific implementations, the ceramsite composition includes:
[0018] 10 to 15 parts by weight of bentonite;
[0019] 20 to 40 parts by weight of the composition described in the above technical solution;
[0020] 30-50 parts by weight of fly ash;
[0021] 1 to 10 parts by weight of red mud.
[0022] The present application also provides a ceramsite prepared from the composition described in the above technical solution.
[0023] In some specific implementations, the bulk density of the ceramsite is 400 kg / m 3 ~600kg / m 3 The water absorption rate is 3-12%, and the cylinder pressure strength is 3.0MPa-6.0MPa.
[0024] The present application also provides a method for preparing ceramsite, characterized in that it comprises the following steps:
[0025] The composition of the technical solution is mixed with water to form balls, and the obtained balls are aged and then dried;
[0026] The dried spherical material is preheated and then calcined, and then cooled to obtain ceramsite.
[0027] In some specific implementations, the drying temperature is 100° C. to 120° C., and the drying time is 100 min to 150 min.
[0028] In some specific implementations, the preheating temperature is 400° C. to 600° C., and the preheating time is 30 min to 60 min;
[0029] The calcination temperature is 1000° C. to 1500° C., and the calcination time is 10 min to 20 min.
[0030] In some specific implementations, the cooling includes:
[0031] First, it is naturally cooled to 500°C to 700°C in a calcining furnace, and then naturally cooled at room temperature.
[0032] In the present application, Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32-45:5-10:9-15 are used as gas-generating substances, and bentonite, fly ash and red mud are used to prepare ceramsite. The gas-generating substances have good gas-generating effects, and can increase the density of the obtained ceramsite and improve its strength when the dosage is low. For example, the bulk density of the ceramsite is 400kg / m 3 ~600kg / m 3 The water absorption rate is 3-12%, and the cylinder pressure strength is 3.0MPa-6.0MPa. DETAILED DESCRIPTION
[0033] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0034] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0035] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0036] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0037] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0038] The present application provides a composition comprising Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32-45:5-10:9-15.
[0039] The composition provided by the present application also includes CaCO3 and free carbon. CaCO3 decomposes at high temperature to generate a large amount of gas, so that closed pores are formed inside the ceramsite, reducing the bulk density of the ceramsite. Free carbon can play a role in combustion support and can also play the role of a reducing agent, for example, it can reduce iron oxide to produce gas (CO2, CO), and the combustion of free carbon will also produce gas, so the free carbon plays the role of a foaming agent, which can effectively reduce the density of the ceramsite, which is conducive to achieving the purpose of firing lightweight ceramsite.
[0040] The applicant has found that in the preparation process of lightweight ceramsite, the free carbon content is an important factor that cannot be ignored. The free carbon content not only affects the physical properties of ceramsite, but is also directly related to its performance in construction and engineering applications. By accurately controlling the proportion of free carbon, the lightweight ceramsite will be promoted to form more pores during the firing process, thereby reducing its bulk density, so that the ceramsite has more advantages in building materials, such as reducing the burden of building structures and improving thermal insulation effects. However, the lower the bulk density of ceramsite, the worse its strength. The present application adds calcium hydroxide to the raw materials, which can regulate the release rate of carbon dioxide, stabilize the ceramsite structure, and avoid a significant decrease in the mechanical properties of ceramsite. Moreover, the presence of calcium hydroxide can inhibit the occurrence of alkali aggregate reaction of lightweight ceramsite to a certain extent. Therefore, when the mass ratio of Ca(OH)2, CaCO3 and free carbon is 32-45:5-10:9-15, not only can the bulk density of ceramsite be reduced, but also the strength of ceramsite can be improved.
[0041] In some specific implementations, the composition includes:
[0042] Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:9;
[0043] or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:12;
[0044] or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:15;
[0045] or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32:5:12;
[0046] Or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 45:5:12.
[0047] The present application also provides a ceramsite composition, comprising:
[0048] 5 to 20 parts by weight of bentonite;
[0049] 10 to 50 parts by weight of the composition described in the above technical solution;
[0050] 20 to 60 parts by weight of fly ash;
[0051] 0 to 30 parts by weight of red mud.
[0052] The ceramsite composition provided in the present application includes bentonite, whose main components are SiO2 and Al2O3. In a typical embodiment, the bentonite includes more than 70% SiO2 and more than 12% Al2O3. In some specific implementations, the amount of the bentonite is 5 to 20 parts by weight, preferably 10 to 15 parts by weight, and more preferably 15 parts by weight.
[0053] The ceramsite composition provided in the present application includes the composition described in the above technical solution, and its usage is 10 to 50 parts by weight, preferably 20 to 40 parts by weight, more preferably 25 to 35 parts by weight, and most preferably 35 parts by weight.
[0054] The ceramsite composition provided in the present application includes fly ash, and its main components are SiO2, Al2O3 and CaO. In a typical embodiment, the fly ash includes: more than 50% SiO2, more than 30% Al2O3 and more than 9% CaO. In some specific implementations, the amount of the fly ash is 20 to 60 parts by weight, preferably 30 to 50 parts by weight, more preferably 35 to 45 parts by weight, and most preferably 40 parts by weight.
[0055] The ceramsite composition provided in the present application includes red mud, and its main components are SiO2, CaO, Fe2O3 and Al2O3. In a typical embodiment, the red mud includes: 23% SiO2, 45% CaO, 23% Fe2O3, 18% Al2O3, etc. In some specific implementations, the amount of the red mud is 0 to 30 parts by weight, preferably 1 to 20 parts by weight, more preferably 1 to 10 parts by weight, and most preferably 3 to 8 parts by weight.
[0056] In some specific implementations, the ceramsite composition includes:
[0057] 10 to 15 parts by weight of bentonite;
[0058] 20 to 40 parts by weight of the composition described in the above technical solution;
[0059] 30-50 parts by weight of fly ash;
[0060] 1 to 10 parts by weight of red mud.
[0061] The present application also provides a ceramsite prepared from the composition described in the above technical solution. In some specific implementations, the ceramsite is spherical or elliptical in shape, has excellent ball-forming properties, and has good gasification effect under high temperature conditions. In some specific implementations, the bulk density of the ceramsite is 400 kg / m 3 ~600kg / m 3 The water absorption rate is 3-12%, and the cylinder pressure strength is 3.0MPa-6.0MPa.
[0062] The present application also provides a method for preparing ceramsite, comprising the following steps:
[0063] The composition of the technical solution is mixed with water to form balls, and the obtained balls are aged and then dried;
[0064] The dried spherical material is preheated and then calcined, and then cooled to obtain ceramsite.
[0065] The present application first mixes the raw materials of the above-mentioned composition evenly, and then mixes with water to form balls. The present application preferably forms balls in a ball-forming disk. The present application has no special restrictions on the rotation speed and angle of the ball-forming disk, as long as it can form balls. In some specific implementations, the particle size of the spherical object obtained after ball-forming is 5 mm to 20 mm.
[0066] After obtaining the spherical object, it is aged, and the aging time is preferably 100 min to 150 min, and more preferably 120 min. After aging, the obtained spherical object is dried in an oven. In some specific implementations, the drying temperature is 100° C. to 120° C., preferably 105° C., and the drying time is 100 min to 150 min, and preferably 120 min.
[0067] After the spherical object is dried, it is preheated and calcined in a muffle furnace. In some specific implementations, the preheating temperature is 400°C to 600°C, preferably 500°C; the time is 30min to 60min, preferably 40min. In some specific implementations, the calcination temperature is 1000°C to 1500°C, preferably 1200 degrees Celsius, and the time is 10min to 20min, preferably 15min.
[0068] After calcination, the ceramsite is cooled to obtain ceramsite. In some specific implementations, the cooling includes: firstly cooling naturally in a calcining furnace (i.e., a muffle furnace) to 500°C to 700°C, and then cooling naturally at room temperature. Specifically, the present application first cools the ceramsite naturally in a muffle furnace to preferably 600°C, then takes out the ceramsite and cools it to room temperature, and then sieves it to obtain ceramsite.
[0069] In the present application, Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32-45:5-10:9-15 are used as gas-generating substances, and bentonite, fly ash and red mud are used to prepare ceramsite. The gas-generating substances have good gas-generating effects, and can increase the density of the obtained ceramsite and improve its strength when the dosage is low. For example, the bulk density of the ceramsite is 400kg / m 3 ~600kg / m 3 The water absorption rate is 3-12%, and the cylinder pressure strength is 3.0MPa-6.0MPa.
[0070] The composition, ceramsite composition, ceramsite and preparation method thereof provided in the present application are further described below in conjunction with embodiments.
[0071] In the following embodiments, the detection method of each parameter is as follows:
[0072] 1. Bulk density test
[0073] Use a standard container, fill the ceramsite evenly to the upper edge of the container, and then weigh it using a balance. The calculation formula is: bulk density = filling weight / container volume. This method can effectively reflect the looseness of ceramsite and the convenience of transportation and storage.
[0074] 2. Water absorption test
[0075] Take a certain amount of ceramsite and use the drying method to remove the surface moisture. Then immerse the ceramsite in water for 24 hours, take it out, gently wipe the surface, and weigh it. The water absorption rate calculation formula is: water absorption rate = (weight after immersion - weight after drying) / weight after drying × 100%. This test evaluates the water retention performance of ceramsite and is suitable for gardening and construction fields.
[0076] 3. Cylinder pressure strength test
[0077] Put the ceramsite into a standard cylinder and apply a certain pressure until the ceramsite breaks, and record the required pressure value. The calculation formula for cylinder pressure strength is: cylinder pressure strength = applied pressure / bottle mouth area. This test can evaluate the ability of ceramsite to resist external forces and ensure safety and stability in practical applications.
[0078] Example 1
[0079] The raw material ratio is calculated by weight as follows: 15 parts of bentonite, 30 parts of solid mixture (the mass ratio of Ca(OH)2, CaCO3 and free carbon is 40:5:9), 5 parts of red mud and 40 parts of fly ash.
[0080] The specific steps of the preparation method are as follows:
[0081] According to the formula, the raw materials are weighed with an electronic scale, stirred evenly, and then an appropriate amount of water is added with a measuring cylinder, stirred evenly again, and then added to the ball-forming plate, and the particle size of the ceramsite balls is controlled to be 5-20 mm. After the molding is completed, the ceramsite is aged for 120 minutes, and then placed in an oven and dried at 105°C for 120 minutes, and then the ceramsite is placed in a muffle furnace with a preheating temperature of 500°C, a preheating time of 40 minutes, a calcination temperature of 1200°C, and a calcination time of 15 minutes; after calcination, the ceramsite is naturally cooled to 600°C in the furnace, and the ceramsite is taken out of the furnace to achieve rapid cooling at room temperature, and then sieved to obtain lightweight ceramsite.
[0082] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0083] Example 2
[0084] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 40:5:12, and the rest is the same as Example 1.
[0085] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0086] Example 3
[0087] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 40:5:15, and the rest is the same as Example 1.
[0088] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0089] Example 4
[0090] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 32:5:12, and the rest is the same as Example 1.
[0091] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0092] Example 5
[0093] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 45:5:12, and the rest is the same as Example 1.
[0094] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0095] Comparative Example 1
[0096] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 40:5:8, and the rest is the same as Example 1.
[0097] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0098] Comparative Example 2
[0099] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 40:5:16, and the rest is the same as Example 1.
[0100] Comparative Example 3
[0101] The difference from Example 1 is that the mass ratio of Ca(OH)2, CaCO3 and free carbon in the solid mixture is 30:5:16, and the rest is the same as Example 1.
[0102] The bulk density, water absorption, apparent density and cylinder pressure strength of the ceramsite were tested. The results are shown in Table 1, which shows the performance test results of the ceramsite provided in the examples and comparative examples of the present application.
[0103] Table 1 Performance test results of ceramsite provided in the examples and comparative examples of the present application
[0104]
[0105] As shown in Table 1, by controlling the amount of calcium hydroxide added in the solid mixture of lightweight ceramsite raw materials, the gas-generating components inside the ceramsite can be regulated and adjusted, and the problem of significant decrease in the mechanical properties of the ceramsite can be improved. The lightweight ceramsite products produced by controlling the carbon content in the solid mixture of lightweight ceramsite raw materials have a decreasing bulk density and an increasing water absorption rate as the carbon content increases, but the cylinder pressure strength decreases. When the free carbon content of the solid mixture is 8%, the bulk density of the ceramsite is high; when the free carbon content of the solid mixture is 16%, the cylinder pressure strength of the ceramsite is low; when the free carbon content of the solid mixture is 9-15%, the bulk density of the ceramsite is 492-556kg / m3, the water absorption rate is 5.4-11.6%, and the cylinder pressure strength is about 3.1-5.3MPa. Therefore, the lightweight ceramsite prepared by controlling the free carbon content of the solid mixture at 9-15% can be comparable to or even better than the existing technology, but saves clay resources on raw materials. Therefore, the solid mixture containing calcium hydroxide and having a free carbon content of 9 to 15% provided by the present invention reduces the cost of raw materials, saves resources, and provides a new raw material approach for the production of high-quality lightweight ceramsite.
[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composition comprising Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32-45:5-10:9-15.
2. The composition according to claim 1, characterized in that include: Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:9; or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:12; or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 40:5:15; or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 32:5:12; Or Ca(OH)2, CaCO3 and free carbon in a mass ratio of 45:5:
12.
3. A ceramsite composition comprising: 5 to 20 parts by weight of bentonite; 10 to 50 parts by weight of the composition according to claim 1 or 2; 20 to 60 parts by weight of fly ash; 0 to 30 parts by weight of red mud.
4. The ceramsite composition according to claim 3, characterized in that include: 10 to 15 parts by weight of bentonite; 20 to 40 parts by weight of the composition according to claim 1 or 2; 30-50 parts by weight of fly ash; 1 to 10 parts by weight of red mud.
5. A ceramsite prepared from the composition according to claim 3 or 4.
6. The ceramsite according to claim 5, characterized in that Its bulk density is 400kg / m 3 ~600kg / m 3 The water absorption rate is 3-12%, and the cylinder pressure strength is 3.0MPa-6.0MPa.
7. A method for preparing ceramsite, characterized in that: The following steps are involved: Mixing the composition according to claim 3 or 4 with water to form balls, aging the obtained balls and then drying them; The dried spherical material is preheated and then calcined, and then cooled to obtain ceramsite.
8. The preparation method according to claim 7, characterized in that: The drying temperature is 100° C. to 120° C., and the drying time is 100 min to 150 min.
9. The preparation method according to claim 8, characterized in that: The preheating temperature is 400°C to 600°C, and the preheating time is 30min to 60min; The calcination temperature is 1000° C. to 1500° C., and the calcination time is 10 min to 20 min.
10. The preparation method according to claim 9, characterized in that: The cooling comprises: First, it is naturally cooled to 500°C to 700°C in a calcining furnace, and then naturally cooled at room temperature.